The constant balancing 6UPS/(3PRRR)+S parallel mechanism and its balancing performance analysis. (August 2018) - Zhao, Yanzhi; Liang, Bowen; Yang, Wei; Wang, Chang; Chen, Guimin; Zhao, Tieshi
Highlights: The constant balancing 6UPS/(3PRRR)+S parallel mechanism is composed of two nested parallel mechanisms, which can achieved the goal to invariant balancing the gravity of payload in the global workspace. The Jacobian matrix of inner 3-PRRR balance mechanism is constant, it can output constant balance force under the condition of just keeping the magnitude and direction of input force of the balance mechanism constant, which does not require the introduction of additional position detection device. In this way, the difficulty in force control is reduced compared with redundant actuation. The proportion of balanced gravity can be adjusted, through the adjustment of the magnitude of input force of the balance mechanism. Abstract: This paper presents a constant balancing 6UPS/(3PRRR)+S parallel mechanism. It is composed of two nested parallel mechanisms: the outer 6-UPS parallel mechanism and the inner 3-PRRR balance mechanism, both of which are connected by a spherical joint. Because the Jacobian matrix of the 3-PRRR balance mechanism is constant, the invariant balancing performance of the 6UPS/(3PRRR)+S parallel mechanism can be achieved by just keeping the input forces of the inner balance mechanism constant at any pose in the global workspace, which has brought great convenience for the application of these mechanisms with good balance characteristics. The dynamics model of the 6UPS/(3PRRR)+S parallel mechanism is established based on the screw theory and the influence coefficient method. Then the μ (balance coefficient) of the mechanism is defined, the balancing performance of this mechanism is analyzed by using the value of F ¯ (average driving force) under the condition of the same balance coefficient. The balancing performance of the 6UPS/6UPS parallel mechanism is compared with that of the 6UPS/(3PRRR)+S parallel mechanism under the condition of the constant input force of the balance mechanism and the constant balance coefficient, consequently, the comparative result proves the excellent global constant balancing performance of the 6UPS/(3PRRR)+S parallel mechanism.